An Analysis of the Public Media Coverage of the Farm Workers Opportunity Project 1969 - American Friends Service Committee::::::; Peter Lauwerys::::::; Christopher Paige:::::: (1969)
An analysis of the Farm Workers Opportunity Project, a federally funded basic education program, and the media coverage of said project.